Dimethyloxalylglycine pretreatment of living donor alleviates both donor and graft liver ischemia-reperfusion injury in rats - Jia, Degong; Zhao, Minjie; Luo, Jiefu; Li, Shengwei; Gong, Jianping; Cheng, Mingxiang (Frontiers in Pharmacology, 2024)
Background: Under the circumstance of the increasing waiting list for liver transplantation, living donor liver transplantation (LDLT) can alleviate the shortage of liver donors to some extent. However, how to reduce both donor and graft ischemia-reperfusion injury (IRI) is still an unsolved problem in LDLT. Hypoxia-induced transcription factor 1 (HIF1) activation is considered an important mechanism of cellular adaptation to hypoxia, and early activation of HIF1 may be a new way to alleviate liver IRI. Therefore, we aimed to investigate the impact of the HIF1 stabilizer dimethyloxalylglycine (DMOG) on IRI and the survival rate of donors and recipients of rat LDLT. Methods: Seventy percent partial liver resection and 30% partial liver transplantation were used to simulate donor and recipient of clinical LDLT. Rats were treated with DMOG (40 mg/kg) or with an equivalent amount of saline. The expression of HIF1 and downstream targets was analyzed after 2 hours of reperfusion. Liver function and histopathology, apoptosis and oxidative stress levels were detected 6 hours after reperfusion. At the same time, the 7-day survival rate of rats was calculated. Results: DMOG pretreatment significantly reduced IR-induced injury in the donor and recipient, which was manifested by reducing liver function damage and promoting tissue recovery. Meanwhile, compared with the untreated group, the oxidative stress level and the cell apoptosis rate were decreased in the group pretreated with DMOG. In addition, the transcription and expression of HIF1 target genes in the DMOG group were significantly enhanced. Remarkably, DMOG also increased the survival rate of the recipient. Conclusions: This study provides the first evidence that DMOG pretreatment of donors significantly alleviates liver IRI in both donors and recipients and increases the survival rate of recipients in LDLT. Therefore, DMOG may be a promising strategy for improving LDLT in the future.